Differences in learning, learning styles and teaching - Grácio, Luísa; Cid, Marilia (My University, 2013)
Cognitive styles and learning styles are both variables that explain the differences between the students and their learning. To sum up, cognitive styles are differential individual patterns of reacting to stimulation received, processing information (i.e., understand and organize) and cognitively facing reality. They are therefore related to the structure of thinking, referring to qualities or modes of knowing, but do not reflect higher or lower intelligence levels. When analyzing an individual, learning style often arises as a key component of being or not able to learn. Thus, those who are responsible for helping others to learn, such as teachers, should identify these styles and adjust to them.
Keywords: Learning Styles; Teaching